Pembelajaran Sistem Online: Tantangan dan Rangsangan - Punaji, Punaji (MAJALAH ILMIAH PEMBELAJARAN, 2007)
Online learning system provides much opportunities to learners to access teaching materials form instructor. There are three key components to support a meaningful interaction: 1) instructional and learning strategies, 2) pedagogical models and construct, and 3) learning technologies. Besides, e-learning includes four feature elements: 1) content relevant to the learning objectives, 2) uses instructional methods , 3) uses media elements, and 4) builds new knowledge and skills.